Experimental and numerical investigation of form-stable dodecane/hydrophobic fumed silica composite phase change materials for cold energy storage. (15th November 2015) - Chen, Jiajie; Ling, Ziye; Fang, Xiaoming; Zhang, Zhengguo
Highlights: Form-stable dodecane/fumed silica composite for cold storage is prepared. A suggesting hypothesis that explains infiltration mechanism is proposed. The performance of the composite phase change material is investigated. Numerical simulation of system is carried out and results fit well. Abstract: A kind of form-stable composite phase change materials used for cold thermal energy storage is prepared by absorbing dodecane into the hydrophobic fumed silica. With relatively suitable pore diameter and hydrophobic groups, hydrophobic fumed silica is beneficial to the penetration and infiltration of dodecane and the leakage problem solving. Scanned by electron micrographs and Fourier transformation infrared, the composite phase change material is characterized to be just physical penetration. Besides, the differential scanning calorimeter and thermo gravimetric analysis reveals the high enthalpy, good thermal stability and cycling performance of this composite phase change material. What's more, Hot-Disk thermal constants analyzer demonstrates that the composite phase change material has low thermal conductivity which is desired in cold storage application. In the experiment, a cold energy storage system is set up and the results from the experiment show that the system has excellent performance of cold storage by incorporating composite phase change material. Apart from that, the experimental data is found to have a great agreement with the numerical simulation which is carried out by using the commercial computational fluid dynamics software FLUENT.